The employee retention among Generation Y at Sime Darby Industrial Sdn. Bhd., Puchong / Nurul Syuhadah Ariadi and Azawarah Abdullah - Ariadi, Nurul Syuhadah; Abdullah, Azawarah (2015)
Recently, the Generation Y is the most demanded employees by employers in any organization, due to characteristic of Generation Y itself. However, it is difficult for employers to retain employees from this generation, because they have their own needs and wants based on their capabilities. To explore this issue, the researchers focus on employee retention decision among Generation Y at Sime Darby Industrial Puchong and the factors influence their decision to retain in the organization. Objective of this study are to determine the relationship between intrinsic, extrinsic and involvement factors toward employee retention decision in Sime Darby Industrial Sdn. Bhd., Puchong. A quantitative study was applied. The researcher instrument involved comprised of a self-administered questionnaire. Simple random sampling was used for this research. There are 298 questionnaires were distributed to Generation Y employees in the organization, and only 176 respondents were returned the questionnaire. Data obtained were analyzed using SPSS version 20.0. The findings of based on Pearson correlation analysis revealed that there are relationship between independent variable (intrinsic motivation factor, extrinsic hygiene factor and involvement factor) and dependent variable (employee retention). While, regression analysis was used to determine the most influence factors that affect employee retention decision among Generation Y at Sime Darby Industrial Sdn. Bhd., Puchong. The results from regression analysis indicate that intrinsic motivation factor is the most influence factors affecting the decision of Generation Y employees to retain in the organization.